Analysis of moral decadent behaviour and student manners in Pesantren - Deriansyah, Ryan; Baharuddin, Mochammad Achwan; Nasaruddin, Razie Bin (Journal of Islamic Education and Innovation, 2024)
Islamic boarding schools are known as educational institutions that teach morals and manners. However, currently the morals and manners of students are experiencing decadence or decline. This is allegedly due to changes in the internal and external community of the Pesantren. The purpose of this study is to analyse the behaviour of deterioration of morals and manners in students in Islamic boarding schools. The research used a qualitative approach by taking data through interviews, observations, and documentation. The validity of the data was analysed by triangulation techniques, then data analysis was carried out by data reduction, data appearance, and conclusions. The results of the study show that the decadence of morals and manners that occur in Pesantren is shown by the behaviour of manners, the attitude of ta'dzim santri to teachers, guests, and parents that decreases. In addition, there are cases of bullying,  violence against fellow students, and acts of theft of goods. There are internal and external factors that are the cause of moral decadent behaviour, internal factors that are related to the personality background of students who are formed in the family and environment before becoming santri in boarding school. External factors, namely the families of students and the environment of students in the boarding schools.